A New Type of Space-position Full-balanced Mechanical Crane and Analysis of Its Comprehensive Performance - Song Ningce; Xie Zhijiang; Liu Fei; Li Liangliang (Jixie chuandong)
The mechanical cranes used widely in industrial and scientific research,but the traditional mechanical cranes can only achieve horizontal balance. A new type of space-position full-balanced mechanical crane composed of multi-parallel quadrilateral rods is presented. It doesn’t need to add other power sources to complete the horizontal and vertical decoupling motion,offset the total load basically,and reach the whole space-position equilibrium. The velocity characteristics are analyzed by the method of velocity instantaneous center,and the simulation verification is carried out by using the ADAMS. The input force performance analysis of the full-balanced mechanical crane is carried out by using the principle of virtual work and simulated by using Matlab,and the full-balanced capacity of space position of the mechanical cranes is verified. The device provides a theoretical basis for the design of smart handling machinery.